Prediction of the performance of off–road tyres. (4th August 2014) - El–Gawwad, K.A. Abd; Crolla, D.A.; Soliman, A M.A.; El–Sayed, F.M.
The prediction of tyre forces is of great interest to both the designers and users of off–road vehicles. The magnitude of tractive force can determine the size of implement which may be pulled and the rate of work. The lateral force controls the steerability and handling of an off–road vehicle. The rolling resistance force should be minimised to make the energy wasted in overcoming motion resistance force as small as possible. In this paper, two types of tyre model, empirical and physical, were examined. An example of each type of tyre models was studied. The multi–spoke tyre model was chosen as a physical based model, while the Magic Formula and the mobility number method, were selected as two different types of empirical model. A comparison between the results of the two types of tyre model for the pure cornering case and pure slip case under the same conditions was made. Computer programs using MATLAB software were developed. The most suitable model to predict off–road tyre forces was selected. The results indicate that the model based on the physical properties, the multi–spoke tyre model, is the preferred model used in this work. It is better for understanding the mechanics of off–road tyres than the empirical models. It can be modified to study the effect of overall off–road tyre characteristics on the performance. The results of the multi–spoke tyre model also open up the opportunity of using it in detailed modelling of different aspects of off–road vehicle dynamics.